2021
DOI: 10.1111/acem.14209
|View full text |Cite
|
Sign up to set email alerts
|

Despair in the time of COVID: A look at suicidal ingestions reported to the California Poison Control System during the pandemic

Abstract: Background Despite concern that the global pandemic will worsen depression and suicide rates, there remain little data on its actual effect. The purpose of this study was to determine the effect of the COVID‐19 pandemic on suicidal ingestions reported to the California Poison Control System (CPCS). Methods This was a cross‐sectional comparison of suicidal ingestions reported to the CPCS during the 2020 COVID‐19 pandemic compared to suicidal ingestions reported during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…Sixteen (16) studies (88.9%) had a cross-sectional design and two studies [ 24 , 26 ] have followed cohort design. Out of 18 studies included, 8 (44.4%) were from the United State of America [ 22 , 24 , 26 , 30 , 32 , 34 , 36 , 38 ], 4 (22.2%) from Japan [ 25 , 27 , 29 , 35 ], 2 (11.1%) from India [ 23 , 37 ] and 1 (5.6%) each from Austria [ 31 ], Canada [ 33 ], German [ 28 ] and Nepal [ 39 ].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen (16) studies (88.9%) had a cross-sectional design and two studies [ 24 , 26 ] have followed cohort design. Out of 18 studies included, 8 (44.4%) were from the United State of America [ 22 , 24 , 26 , 30 , 32 , 34 , 36 , 38 ], 4 (22.2%) from Japan [ 25 , 27 , 29 , 35 ], 2 (11.1%) from India [ 23 , 37 ] and 1 (5.6%) each from Austria [ 31 ], Canada [ 33 ], German [ 28 ] and Nepal [ 39 ].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The main characteristics of the included studies are listed in Table 1. Some of the studies' studied samples were composed only of suicidal attempts or suicidal deaths [22][23][24][25][26][27][28][29], while some of the studies included a wider sample to see the incidence of suicidal deaths and suicidal attempts [30][31][32][33][34][35][36][37][38]. The sample sizes of the studies that included only the suicidal deaths or suicidal attempts were ranged from 53 to 17,794.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Of note, ingestions are involved in approximately 80% of all suicide attempts presenting to hospitals [ 26 ]. To our knowledge, only one study has used PCC data to assess the impact of the pandemic, this showing decreased numbers of calls in California in 2020 compared to 2019 and 2018 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our first objective was to assess trends in calls for suicide attempts during the COVID-19 pandemic (until May 31 st , 2022) as compared to pre-pandemic years, using national data on calls to PCCs with regard to intentional ingestion of drugs or other toxic substances. We also aimed to investigate the relevance of using calls to PCCs as a means of monitoring suicide attempts at the national level [ 27 ]. Based on available data, we hypothesized an initial decrease in calls to PCCs mirroring data on self-harm hospitalizations, followed by a rebound in young people during the subsequent stage of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Findings varied depending on the outcomes. The rate of suicides was not observed to increase during the pandemic 32,38,45,59,61,90 , though some studies indicated a potential drop in comparison to pre-pandemic years [26][27][28]33,46,49,51,52,58,62,89,91 . There were only a few countries, such as Japan, reported contradictory results for suicide.…”
Section: Discussionmentioning
confidence: 96%